Mining Marketplaces: Exponents of Urban Development of Medieval Serbia - Zarković, Božidar (Collection of Papers of the Faculty of Philosophy in Priština, 2021)
The paper follows the formation and the rise of mining marketplaces in Medieval Serbia and their contribution to the urban development of the country. In addition to mining marketplaces in Serbia, there were others as well, but the mining marketplaces experienced the highest rise and the greatest urban development. Present urban elements bear witness to the fact that that they were modern elements in those times. Their rise was discontinued, as well as the development of Medieval Serbian state in the middle of the 15th century.
Keywords: mining marketplaces; the Middle Ages; urban settlements; development; Serbia